1997
DOI: 10.1046/j.1365-313x.1997.11061325.x
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis thaliana cDNA complementing a hamster apoptosis suppressor mutant

Abstract: Programmed cell death or apoptosis is a process in which unwanted cells are eliminated during growth and development. In mammals, several genes have been identified whose products are necessary to prevent entry into the apoptotic process. We have isolated a clone from an Arabidopsis thaliana cDNA library whose predicted translation product shows highly significant similarity to the mammalian defender against apoptotic death 1 (DAD1) protein. Transformation of the mutant hamster tsBN7 cells, which undergo apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 0 publications
0
81
0
1
Order By: Relevance
“…In plants, a distinct role in the glycosylation of proteins has been shown for STT3A and DGL1 (Koiwa et al, 2003;Lerouxel et al, 2005). Other proteins with homology to mammalian/yeast OST subunits have been identified, but their involvement in the transfer of oligosaccharides to proteins has not been reported (Gallois et al, 1997;Danon et al, 2004;Johnson et al, 2004). The importance of this protein complex for plants is also underlined by the fact that the dgl1 null alleles as well as plants completely deficient in STT3 (stt3a stt3b double knockouts) are not viable.…”
Section: Arabidopsis Ost3/6 Is a Putative Ortholog Of Yeast Ost3p Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, a distinct role in the glycosylation of proteins has been shown for STT3A and DGL1 (Koiwa et al, 2003;Lerouxel et al, 2005). Other proteins with homology to mammalian/yeast OST subunits have been identified, but their involvement in the transfer of oligosaccharides to proteins has not been reported (Gallois et al, 1997;Danon et al, 2004;Johnson et al, 2004). The importance of this protein complex for plants is also underlined by the fact that the dgl1 null alleles as well as plants completely deficient in STT3 (stt3a stt3b double knockouts) are not viable.…”
Section: Arabidopsis Ost3/6 Is a Putative Ortholog Of Yeast Ost3p Andmentioning
confidence: 99%
“…A mutant line with a weak dgl1 allele displayed reduced protein N-glycosylation efficiency consistent with a crucial role of DGL1 in plant OST function. In addition, Arabidopsis proteins have been identified that display significant homology to yeast Swp1p/mammalian ribophorin II (HAPLESS6 [HAP6]) and OST2/defender-against apoptotic death (DAD1 and DAD2; Gallois et al, 1997;Danon et al, 2004;Johnson et al, 2004). Arabidopsis DAD1 could rescue the apoptotic phenotype of a mutant hamster cell line, indicating a conserved function between animals and plants (Gallois et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways may be different than the ones existing in animals, since transgenic tobacco plants carrying the Bcl-X L gene do not show altered response to the TMV virus or to P. syringae . Functional homologues of the animal anti-cell death dad-1 gene (Gallois et al, 1997;Sugimoto et al, 1995) have recently been found in maize, rice and Arabidopsis, but their involvement in the HR remains to be established. Additionally, plant proteins with conserved domains of the animal ced-9/Bcl-2 protein family have yet to be described.…”
Section: Protectant Mechanisms and Anti-cell Death Pathwaysmentioning
confidence: 99%
“…Ce-dad-1 is 62%, AtDAD1 is 51.5%, riceDAD1 is 47.3%, and yeast Ost2p is 40%, identical to human/hamster DAD1. Except for the yeast OST2 gene, all the other homologues have been found to complement tsBN7 cells (Sugimoto et al 1995;Gallois et al 1997;T. Makishima, personal communication), indicating that the DAD1 protein is both structurally and functionally well conserved.…”
Section: Introductionmentioning
confidence: 98%